Neurophysiological Comparison Among Tonic, High Frequency, and Burst Spinal Cord Stimulation: Novel Insights Into Spinal and Brain Mechanisms of Action. Issue 5 (4th January 2018) - Bocci, Tommaso; De Carolis, Giuliano; Paroli, Mery; Barloscio, Davide; Parenti, Laura; Tollapi, Lara; Valeriani, Massimiliano; Sartucci, Ferdinando
Abstract : Rationale: Spinal cord stimulation (SCS) is an effective option for neuropathic pain treatment. New technological developments, as high‐frequency (HF) and theta burst stimulation (TBS), have shown promising results, although putative mechanisms of action still remain debated. Methods: thirty patients with lower back pain were enrolled and underwent LF, HF, and TBS. Laser evoked potentials (LEPs) were recorded by using a Nd:YAG laser. Amplitudes and latencies of the main two components (N1, N2/P2) were compared among different experimental sessions. Changes in resting motor threshold (RMT), cortical silent period (cSP), short intracortical inhibition (SICI), and intracortical facilitation (ICF) were also evaluated. Results: TBS dampened LEP amplitudes compared with LF (N1: p  = 0.032; N2/P2: p  < 0.0001) and HF stimulation (N1: p  = 0.029; N2/P2: p  < 0.0001, Holm‐Sidak post‐hoc test). Concurrently, TBS increased N1 latency, when compared with baseline and LF stimulation ( p  = 0.009 and 0.0033). Whereas RMT and SICI did not change among experimental conditions, TBS significantly prolonged cSP duration compared with baseline ( p  = 0.002), LF ( p  = 0.048), and HF‐SCS ( p  = 0.016); finally, both HF ( p  = 0.004) and TBS ( p  = 0.0039) increased ICF. Conclusion: TBS modulates medial and lateral pain pathways through distinct mechanisms, possibly involving both GABA(a)ergic and Glutamatergic networks at an intracortical level. These results may have implications for therapy and for the choice of best stimulation protocol.